A literature review: Enhance students’ physical literacy (Journal of Physical Education Health and Sport, 2023)
At the moment, Indonesia is moving into the endemic phase. For information on healthy living in the world of education. The purpose of this study is to highlight the value of physical literacy as a means of embracing this time of transition. At this time, there is no clear correlation between the online sports learning process and the field-based lectures themselves. It is necessary to promote physical literacy in order to boost physical activity. Sports learning will therefore function effectively. The study conducted a thorough review of many articles on physical literacy. A total of 12 studies were included in this review. The outcome is that, in general, physical literacy will be better applied right away, specifically when the child is still a young child.